Techniki perswazyjne w prasowych tekstach o modzie na przykładzie kobiecych czasopism „Twój Styl”, „Świat Kobiety” oraz męskiego magazynu „Men’s Health” (roczniki 2005, 2006, 2007) - Olejnik, Ewelina (Acta Universitatis Lodziensis. Folia Linguistica, 2010)
The basic of this research is vocabulary used in women’s magazines such as “Twój Styl” and “Świat Kobiety” and also in „Men’s Health” magazine (of which target group are men). Superior aim of the article is to show persuasion techniques, which are stimulating attitudes that should accompany desirable behaviours. Comparison analysis enabled to indicate similarities and differences in the way of persuasive realization of texts about fashion directed to both sexes/genders. For the sake of inner stratification of persuasion techniques and wide range of examples there has been done a review based on a mixed criteria. That enabled to present the persuasion issue in many contexts. On the basics of language material there has been presented following groups: Semantic Categories, Grammar Means, Lexical Means. Metaphor is incredibly productive example of persuasion techniques. Its specific case, which is personification, is the basic of four metaphoric models specified in this part: Metaphor of power, Metaphor based on the human relationships scheme, Metaphor of life’s stages, Metaphor of living in the world of culture and art. The last separated way of persuasion is to use image as a technique that is accompanying language strategies – especially characteristic and suggestive phenomenon which is easy to be seen in fashion texts. Semantic categories partially enabled to put in order language persuasion techniques. In vocabulary of women’s fashion as well as in vocabulary of men’s one, they are represented very strongly which is confirmed by the size of the part dedicated to them. The category of neutrality has turned out to be more representative for men’s fashion vocabulary. On the other hand realization of erotic category has appeared in texts for women only. One could separate grammatical-morphological and lexical means of persuasion from all analysed magazines. In the summary the author says that all the stereotypes, ways of thinking and judgements of specific phenomenons from the world of fashion are being copied by creating and consolidating words connotations.